Analytical profile of the lysergamide 1cP‐AL‐LAD and detection of impurities. Issue 3 (3rd December 2022) - Kavanagh, Pierce V.; Westphal, Folker; Pulver, Benedikt; Schwelm, Hannes M.; Stratford, Alexander; Auwärter, Volker; Chapman, Stephen J.; Halberstadt, Adam L.; Brandt, Simon D.
Abstract: The development of novel lysergamides continues to occur, based on both the needs of psychedelic medicine and commercial interest in new recreational substances. The present study continues the authors' research on novel lysergamides and describes the analytical profile of 1‐cyclopropanoyl‐AL‐LAD (IUPAC name: 1‐(cyclopropanecarbonyl)‐ N, N ‐diethyl‐6‐(prop‐2‐en‐1‐yl)‐9, 10‐didehydroergoline‐8β‐carboxamide; 1cP‐AL‐LAD), using various chromatographic, mass spectrometric, and spectroscopic methods. Analysis of a powdered sample of 1cP‐AL‐LAD, obtained from an online vendor, by high performance liquid chromatography‐electrospray ionization‐quadrupole time‐of‐flight mass spectrometry in full scan/AutoMS/MS mode revealed the detection of 17 impurities based on high‐resolution tandem mass spectral data; tentative determination of their identity was based on mass spectral grounds alone, though detection of AL‐LAD and 1P‐AL‐LAD was confirmed using available reference standards. Other tentative compound identifications included 1‐acetyl‐AL‐LAD and several other substances potentially reflecting oxidation of the N 6 ‐allyl group as well as other positions on the ergoline ring system. These data may assist those interested in the chemistry of lysergamides. Finally, 1cP‐AL‐LAD was also detected in samples of "blotters" sold online for recreational use. Abstract : An analytical profile of 1cP‐AL‐LAD using chromatographic, mass spectrometric and spectroscopic methods, and detection of 17 impurities based on analysis by LC‐QTOF‐MS/MS. Detections included AL‐LAD, 1P‐AL‐LAD, and other compounds, such as those potentially reflecting various oxidative changes that might have occurred during synthesis.